At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To determine which table contains points that lie on the graph of the function [tex]\( h(x) = \sqrt[3]{-x + 2} \)[/tex], we can substitute each [tex]\( x \)[/tex] value from each table into the function [tex]\( h(x) \)[/tex] and compare the results with the corresponding [tex]\( y \)[/tex] values. Let's go through each table one by one and perform these calculations.
### Table 1
For [tex]\( x = -8 \)[/tex], [tex]\( y = 4 \)[/tex]:
[tex]\[ h(-8) = \sqrt[3]{-(-8) + 2} = \sqrt[3]{8 + 2} = \sqrt[3]{10} \approx 2.154 \neq 4 \][/tex]
### Table 2
For [tex]\( x = -2 \)[/tex], [tex]\( y = 10 \)[/tex]:
[tex]\[ h(-2) = \sqrt[3]{-(-2) + 2} = \sqrt[3]{2 + 2} = \sqrt[3]{4} \approx 1.587 \neq 10 \][/tex]
### Table 3
For [tex]\( x = -6 \)[/tex], [tex]\( y = 2 \)[/tex]:
[tex]\[ h(-6) = \sqrt[3]{-(-6) + 2} = \sqrt[3]{6 + 2} = \sqrt[3]{8} = 2 \][/tex]
For [tex]\( x = 1 \)[/tex], [tex]\( y = 1 \)[/tex]:
[tex]\[ h(1) = \sqrt[3]{-(1) + 2} = \sqrt[3]{1} = 1 \][/tex]
For [tex]\( x = 2 \)[/tex], [tex]\( y = 0 \)[/tex]:
[tex]\[ h(2) = \sqrt[3]{-(2) + 2} = \sqrt[3]{0} = 0 \][/tex]
For [tex]\( x = 3 \)[/tex], [tex]\( y = -1 \)[/tex]:
[tex]\[ h(3) = \sqrt[3]{-(3) + 2} = \sqrt[3]{-1} = -1 \][/tex]
For [tex]\( x = 10 \)[/tex], [tex]\( y = -2 \)[/tex]:
[tex]\[ h(10) = \sqrt[3]{-(10) + 2} = \sqrt[3]{-8} = -2 \][/tex]
The values from Table 3 exactly match the computed values, therefore:
[tex]\[ \boxed{\text{Table 3}} \][/tex]
### Table 4
For [tex]\( x = -4 \)[/tex], [tex]\( y = -8 \)[/tex]:
[tex]\[ h(-4) = \sqrt[3]{-(-4) + 2} = \sqrt[3]{4 + 2} = \sqrt[3]{6} \approx 1.817 \neq -8 \][/tex]
After carefully examining the computations, we see that only Table 3 correctly represents the points on the graph of [tex]\( h(x) = \sqrt[3]{-x + 2} \)[/tex]. Thus, the correct answer is Table 3.
### Table 1
For [tex]\( x = -8 \)[/tex], [tex]\( y = 4 \)[/tex]:
[tex]\[ h(-8) = \sqrt[3]{-(-8) + 2} = \sqrt[3]{8 + 2} = \sqrt[3]{10} \approx 2.154 \neq 4 \][/tex]
### Table 2
For [tex]\( x = -2 \)[/tex], [tex]\( y = 10 \)[/tex]:
[tex]\[ h(-2) = \sqrt[3]{-(-2) + 2} = \sqrt[3]{2 + 2} = \sqrt[3]{4} \approx 1.587 \neq 10 \][/tex]
### Table 3
For [tex]\( x = -6 \)[/tex], [tex]\( y = 2 \)[/tex]:
[tex]\[ h(-6) = \sqrt[3]{-(-6) + 2} = \sqrt[3]{6 + 2} = \sqrt[3]{8} = 2 \][/tex]
For [tex]\( x = 1 \)[/tex], [tex]\( y = 1 \)[/tex]:
[tex]\[ h(1) = \sqrt[3]{-(1) + 2} = \sqrt[3]{1} = 1 \][/tex]
For [tex]\( x = 2 \)[/tex], [tex]\( y = 0 \)[/tex]:
[tex]\[ h(2) = \sqrt[3]{-(2) + 2} = \sqrt[3]{0} = 0 \][/tex]
For [tex]\( x = 3 \)[/tex], [tex]\( y = -1 \)[/tex]:
[tex]\[ h(3) = \sqrt[3]{-(3) + 2} = \sqrt[3]{-1} = -1 \][/tex]
For [tex]\( x = 10 \)[/tex], [tex]\( y = -2 \)[/tex]:
[tex]\[ h(10) = \sqrt[3]{-(10) + 2} = \sqrt[3]{-8} = -2 \][/tex]
The values from Table 3 exactly match the computed values, therefore:
[tex]\[ \boxed{\text{Table 3}} \][/tex]
### Table 4
For [tex]\( x = -4 \)[/tex], [tex]\( y = -8 \)[/tex]:
[tex]\[ h(-4) = \sqrt[3]{-(-4) + 2} = \sqrt[3]{4 + 2} = \sqrt[3]{6} \approx 1.817 \neq -8 \][/tex]
After carefully examining the computations, we see that only Table 3 correctly represents the points on the graph of [tex]\( h(x) = \sqrt[3]{-x + 2} \)[/tex]. Thus, the correct answer is Table 3.
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.